Online Health Navigation: Study Case of @leonavictoria_ahligizi’s Instagram's Impact on Information Fulfilment for Stunting Prevention - Reza Gustifa, Adinda; Windah, Andi; Tina, Kartika; Nurhaida, Ida; Aryanti, Nina Yudha (International Journal of Health Engineering and Technology, 2024)
This study investigates the impact of Instagram content on maternal attitudes and practices pertaining to child nutrition and the prevention of stunting. The study utilizes case study approach to analyze the Instagram account @leonavictoria_ahligizi on Milhinhos's theoretical framework. The research assesses the content of the account in terms of its relevance, accuracy, value, understandability, discoverability, and consistency. The analysis is contingent upon Instagram's capacity to address a variety of informational requirements, including cognitive, affective, personal integration, social integration, and tension release. The findings illustrate a statistically significant influence of Instagram in improving the dietary practices of mothers of preventing stunting in children. The findings analysis, utilizing SmartPLS 4. 0, revealed a significant association between Instagram content and users' understanding and dietary habits, as evidenced by a path coefficient of 0. 729 This suggests a substantial impact on the satisfaction of information needs. The demographic data indicates that the majority of the participants are well-educated mothers between the ages of 25 and 34, who are actively involved in consuming the content with the aim of enhancing their children's dietary habits. The material presented on @leonavictoria_ahligizi not only serves to increase knowledge and understanding but also facilitates the practical application of nutritional regimens essential for the early developmental phases of children. This highlights the significant importance of customized, trustworthy, and practical social media material in addressing child stunting and advancing public health by promoting informed dietary habits. The incorporation of social media platforms into health education initiatives signifies a substantial advancement in efforts to combat worldwide malnutrition and improve the health outcomes of communities.